Key Challenges in Rural Development: Bringing economics, management and social sciences into practice - ELLS Summer School Proceedings - Hans Karl Wytrzens (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2016)
The proceedings "Key Challenges in Rural Development: Bringing economics, management and social sciences into practice" highlight some selected aspects of a complex topic presenting individual contributions of six doctoral students who participated in the Euroleague for Life Sciences (ELLS) Summer School in Vienna, Austria from July 3-9, 2016. The facets range from "The global in the local: The role of social movements in food sovereignty diffusion in the Philippines" and "Extensive farming and its impacts on the sustainable development: The thesis of development of economic activities in rural areas in the context of European Union sustainable development" to "The role of local government in the financing of rural development for the example of Garwoliński district" furthermore "Diversification of activities of agriculture holdings: A discussion of the theoretical basis" and "Rural business knowledge exchange and innovation: The contribution of rural enterprise hubs" and finally "Economically motivated adulteration of honey and its incidence in EU-28 in 2002 – 2015".
Keywords: R58; 330; rural development; global change; spatial research; regional policy